Ultrasound evaluation of development of olfactory sulci in normal fetuses: a possible role in diagnosis of CHARGE syndrome. (August 2016) - Acanfora, M. M.; Stirnemann, J.; Marchitelli, G.; Salomon, L. J.; Ville, Y.
ABSTRACT: Objectives: To describe the timing of the ultrasound appearance of olfactory sulci in normal fetuses, according to gestational age. Methods: Olfactory sulci were assessed prospectively in the coronal plane on routine brain ultrasound examination in 100 normal fetuses between 22 and 31 + 6 weeks' gestation. Examinations were divided into five groups according to gestational age: Group 1, 22 to 23 + 6 weeks ( n  = 22); Group 2, 24 to 25 + 6 weeks ( n  = 9); Group 3, 26 to 27 + 6 weeks ( n  = 25); Group 4, 28 to 29 + 6 weeks ( n  = 22) and Group 5, 30 to 31 + 6 weeks ( n  = 22). For each fetus, olfactory sulci were assessed as absent, developing or formed. Results: Developing sulci appeared as primitive smooth depressions in the frontal lobe, which evolved into deep sharp complete sulci in later pregnancy. It was possible to assess the development of sulci in all cases. Olfactory sulci were consistently absent in Group 1. In Group 2, 44.4% of fetuses had absent olfactory sulci and 55.6% had developing sulci. In Group 3, the olfactory sulci were still developing in 21 (84.0%) fetuses and were completely formed in four (16.0%). Sulci were completely formed in all fetuses in Groups 4 and 5. Conclusions: Fetal brain ultrasound can visualize developing olfactory sulci from as early as 24 weeks' gestation. After 26 weeks, fetuses have detectable olfactory sulci and, after 28 weeks, they are completely formed. Abnormal development of olfactory sulci is a key feature of CHARGE syndrome. These results may help to improve the prenatal diagnosis of CHARGE syndrome. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.